Numerical simulation of landslide-generated impulse wave - 赵兰浩 毛佳 刘晓青 李同春 (Journal of hydrodynamics. Series B, 2014)
A numerical model is proposed for the simulation of impulse waves generated by landslides. The fluid-like landslide is modeled as a generalized non-Newtonian visco-plastic fluid. The conservative level set method is extended to the n-phase flow and applied to capture the interfaces of air, water and landslide. Numerical results show an excellent performance of the current model to capture the whole process of the landslide and the impulse wave generation.